ANALISIS PERDAGANGAN BBM PASCA PENETAPAN KENAIKAN HARGA BERDASARKAN PERSPEKTIF ETIKA BISNIS ISLAM - Riki, Muchamad; Makhtum, Ahmad (Jurnal Ekonomika dan Bisnis Islam, 2023)
The increase in the price of fuel oil (BBM) on September 3, 2022 had a big impact on society, besides that this increase allows the appearance of deviant behavior by traders, such as retail traders. The importance of ethics in trading must be carried out, in order to avoid deviant acts and get the pleasure of Allah SWT. Therefore, this study aims to analyze the trading of fuel after the determination of price increases based on the perspective of Islamic business ethics. This research is a qualitative research with a descriptive approach. The type of research used is field research. Data collection techniques used are observation, interviews, and documentation. The results of this study show that the mechanism for trading fuel after the determination of the price increase was carried out by retail traders in Gedangan, Kedungrejo, Kedungadem, Bojonegoro including: buying fuel at gas stations and agents; dosage determination; pricing; and direct marketing. Fuel trading practices carried out by retail traders are not in accordance with Islamic business ethics, namely the principles of equilibrium, free will, responsibility and benevolence. This is because traders are dishonest and commit fraud in the form of reducing the dose of fuel, so that it can harm the buyer.